2019
DOI: 10.1021/acs.oprd.9b00374
|View full text |Cite
|
Sign up to set email alerts
|

Enabled Process To Synthesize Monobactam 1 for Early Development

Abstract: An efficient process to synthesize Monobactam 1 from intermediates 2, 3, and 4 was developed. The process was initially enabled to deliver 500 g of 1 for exploratory toxicity studies and further improved to facilitate kilogram-scale production of the active pharmaceutical ingredient with enhanced quality and throughput. Highlights of the process encompass utilizing 1,1′-carbonyldiimidazole to construct a urea linker with good selectivity, oxidative cleavage to remove a 2,4-dimethoxybenzyl protecting group, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Sulfur trioxide (SO 3 )–DMF complex has found wide applications as a sulfonation reagent and been employed in large scale N-sulfations . However, it has been reported that a bottle of SO 3 –DMF complex exploded during storage .…”
Section: Potential Safety Hazards With Dmfmentioning
confidence: 99%
“…Sulfur trioxide (SO 3 )–DMF complex has found wide applications as a sulfonation reagent and been employed in large scale N-sulfations . However, it has been reported that a bottle of SO 3 –DMF complex exploded during storage .…”
Section: Potential Safety Hazards With Dmfmentioning
confidence: 99%